Determining risk factors in a metal construction workshop - Andrei Dimitescu; Claudiu Babiş (Journal of Research and Innovation for Sustainable Society)
A metal fabrication workshop can produce an extremely varied range of products: gates, fences, railings, interior and exterior stairs, metal shelves, grills, awnings, window blinds, grilles, metal cabinets, warehouse furniture, pallet racks, archive shelves, mobile shelves, universal shelves, modular shelves, specialized shelves, store shelves, advertising boards, special profile poles, demountable structures, metal doors, metal windows, kiosks, containers, tanks, metal hand tools, hardware, metal packaging, metal barracks, metal halls or even accessories for agricultural machinery and utility vehicles.